2017
DOI: 10.1051/0004-6361/201731534
|View full text |Cite
|
Sign up to set email alerts
|

Rayleigh-Taylor instabilities with sheared magnetic fields in partially ionised plasmas

Abstract: Aims. In the present study we investigate the nature of the magnetic Rayleigh-Taylor instability appearing at a tangential discontinuity in a partially ionised plasma when the effect of magnetic shear is taken into account. Methods. The partially ionised character of the plasma is described by the ambipolar diffusion in the induction equation. The dynamics of the plasma is investigated in a single-fluid approximation. After matching the solutions on both sides of the interface we derive a dispersion equation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…It has been shown that ambipolar diffusion allows one to damp incompressible magnetic waves and currents as well as to convert magnetic perturbations into plasma thermal energy (this additional energy can be spent both in the ionization of the plasma and in the actual increase of the plasma temperature, see Khomenko et al 2018). Ambipolar diffusion also modifies the growth rates of instabilities (Soler et al 2012;Díaz et al 2014;Khomenko et al 2014b;Ballai et al 2017;Ruderman et al 2018), and it affects the amount of the emerged flux through the surface (Leake & Arber 2006;Arber et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that ambipolar diffusion allows one to damp incompressible magnetic waves and currents as well as to convert magnetic perturbations into plasma thermal energy (this additional energy can be spent both in the ionization of the plasma and in the actual increase of the plasma temperature, see Khomenko et al 2018). Ambipolar diffusion also modifies the growth rates of instabilities (Soler et al 2012;Díaz et al 2014;Khomenko et al 2014b;Ballai et al 2017;Ruderman et al 2018), and it affects the amount of the emerged flux through the surface (Leake & Arber 2006;Arber et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Since solar prominences have often temperatures that are not high enough for a complete ionisation of the plasma, the effect of partial ionisation on the generation and evolution of MRT instabilities was also studied by (e.g. Diaz et al (2014), Ruderman et al (2017)). These investigations showed that the MRT instability becomes sensitive to the degree of plasma ionisation only for plasmas with small values of plasma beta and in a very weakly ionised state.…”
Section: Introductionmentioning
confidence: 99%
“…They found that in the partially ionised case the plasma is always unstable and the growth rate for partially ionised plasmas is 50% larger than in the fully ionised case. The same problem of RTI was later analysed by Ruderman et al (2018), however they allowed the magnetic field to have a shear with respect to the direction of wave propagation. Their results show that the RTI becomes sensitive to the plasma ionisation degree only for plasmas corresponding to small values of plasma-beta and predominantly neutral plasma.…”
Section: Introductionmentioning
confidence: 99%